Study on the refractive errors of school going children of Pokhara city in Nepal - Niroula, DR; Saha, CG (Kathmandu University Medical Journal, 2009)
Objectives: Refractive errors are the one of the most common visual disorders found worldwide in school going children and it is also one of the causes of blindness. It can easily be prevented, if timely proper measures are taken. In Kathmandu valley and Mechi Zone of Nepal, the distribution of refractive errors was found to be very high. No records are available from the Western part of Nepal. Considering the importance of the refractive errors the present study had been undertaken in Pokhara city. Materials and methods: Nine hundred and sixty four subjects (474 boys, 490 girls) were selected between age groups 10 to 19 years from six schools representing different region of Pokhara. After Preliminary examination: on acuity of vision with Snellen's and Jaeger's charts, the subjects were referred to the Manipal Teaching Hospital, Pokhara for confirmation of the refractive errors. Results: Sixty two schools children (6.43%), out of 964 had refractive errors. Myopia was found to be most common (4.05%). The refractive errors were found more in Private school children (9.29%) than Government school children (4.23%), which is statistically significant (P < 0.05). More boys (7.59%) were found to have suffered from refractive errors than girls (5.31%). Further, children with vegetarian diet (10.52%) had greater number of refractive errors than non-vegetarian diet children (6.17%). Conclusion: In the present study, percentage distribution of myopia was found to be higher (4.05%) than the hyperopia (1.24%) and astigmatism (1.14%). Interestingly, in the present study the refractive errors were found significantly higher in Private schools children than Government schools because the children who read in Private schools have higher socioeconomic status; spend more time in home work, watching Television and Computer as compared to government schools children. These near activities of the eyes causes stress on eyes of the children and might be one of the causes of developing myopia. Key words: Refractive errors, Nepal, Myopia, Hyperopia doi: 10.3126/kumj.v7i1.1769 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 67-72